2021
DOI: 10.1155/2021/9913297
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Performance of Rubber Concrete in Hygrothermal Environment

Abstract: It is widely accepted that the rubber concrete (RC) originating from waste is a promising material that can contribute to the conservation and rational use of natural resources and the protection of the environment. However, the fatigue performance in a hygrothermal environment is a major concern because little pertinent information is available in the relevant literature. In this study, a cyclic loading test was carried out on RC subjected to different wet-dry cycles at different temperatures. The loading str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…During the compaction stage, the pores are in the process of being compacted and closed. As the pores are gradually compacted, the specimens are uniformly compressed and the stress-strain curve increases approximately linearly, indicating the near-elastic stage [12]. During the compaction stage, the curve for the test group incorporating rubber powder with modified pasture fiber was on the lower side of the JZ, indicating that the incorporation of rubber powder with modified pasture fiber resulted in the formation of more internal pores and cracks within the concrete.…”
Section: Stress-strain Curvementioning
confidence: 98%
See 1 more Smart Citation
“…During the compaction stage, the pores are in the process of being compacted and closed. As the pores are gradually compacted, the specimens are uniformly compressed and the stress-strain curve increases approximately linearly, indicating the near-elastic stage [12]. During the compaction stage, the curve for the test group incorporating rubber powder with modified pasture fiber was on the lower side of the JZ, indicating that the incorporation of rubber powder with modified pasture fiber resulted in the formation of more internal pores and cracks within the concrete.…”
Section: Stress-strain Curvementioning
confidence: 98%
“…In the −30 °C environment, the loss rate of rubber powder concrete ductility index is lower than that of ordinary concrete and the rubber powder enhances the ductility of concrete in a low-temperature environment [11]. In the 60 °C environment, plastic deformation is mainly caused by pores and cracks in the cement matrix due to the sound elasticity of the rubber particles [12]. In a Cl-erosion environment, rubber concrete with rubber powder particle size of 3-6 mm and 5% admixture has a denser internal structure than normal concrete, due to the addition of rubber powder improving the microcrack structure of rubber concrete [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, rubber concrete is not widely used as a support material in roadway support structures. However, rubber concretes with lower density, higher energy dissipation, and toughness could be used to support high-ground stress soft rock roadways, as they could meet the demands of relieving the pressure of the surrounding rock [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The application of rubber concrete can alleviate the environmental pollution caused by discarded tires to a certain extent, and has broad application prospects [10]. Liu Yushan et al [11] studied the fatigue resistance of rubber concrete in a dry-wet alternating environment and found that rubber concrete showed better elasticity than ordinary concrete. Zhang Juntao et al [12] studied the frost resistance of rubber concrete under the action of freeze-thaw cycles.…”
Section: Introductionmentioning
confidence: 99%